ASURANSI KESEHATAN INDIVIDU PERAWATAN RUMAH SAKIT - Wilandari, Yuciana (MATEMATIKA, 2007)
The Individual Insurance Health of the Hospital Care is a cooperation form to reduce hospital expenses. The calculation of the annual net premium is influenced by age and sex at the policy released time. The premium can be paid once in each year by renewing the premium every year and also cannot be renewed. Â